PERANCANGAN APLIKASI SMART SEMINAR DAN WORKSHOP BERBASIS WEBSITE - Abdul Hamid Arribathi; Saryani Saryani; Haris Haris (UNIVERSITAS RAHARJA, 2019)
Seminars and workshops are inseparable activities from the world of education in higher education. As the implementation of the Tridharma of Higher Education is teaching, research and service. The results of the research conducted require publication through writing or seminars and workshops. However, there are still many seminars and workshops that hold it conventionally starting from the announcement of the event, registration of participants, to the process of implementing the event. So that it feels less effective. Therefore a Smart Seminar and web and Android based Workshop system is needed, which can facilitate the announcement of events and registration of participants online, absent attendees with QRCode, and make participants able to ask questions directly through the application without interrupting the content being conveyed by the speaker. The research method that was carried out in the first stage was collecting data and information through interviews, literature studies, and Focus Group Discussion (FGD) with seminar and workshop experts. The second stage is to build the system using the Waterfall type SDLC (System Development Life Cycle) method. The Waterfall Model provides a sequential or sequential software lifecycle approach starting from analysis, design, coding, testing, and maintenance. The results of the Smart Seminar and Worksop system design can facilitate educational institutions in conducting seminars and workshops effectively and more quality, as well as more interactive between participants and speakers in terms of questions and answers. This application can be accessed via a web browser or with an Android application.